Adopsi E-Wallet: Utaut2 Diperluas Dengan Kepercayaan - Fernando, Ronal; Putri, Seprianti Eka (Universitas Islam Kadiri, 2023)
Electronic money means the latest financial innovation for payment transactions in Indonesia. There are a variety of electronic wallets in Indonesia offered by banks and non-banks which make it easy for users to carry out transactions via smartphone. This research will review the ability to influence consumer behavioral intentions towards e-wallet services, with the aim of measuring, as well as increasing,acceptance of these systems and customer adoption. The model used for this analysis, Unified Theory of Acceptance and Use of Technology2 (UTAUT2), additional ideas are presented here to replace Social Influence factors with Trust factors to facilitate individual views regarding behavioral intentions in the consumer environment. This research uses a quantitative approach with Purposive Sampling techniques. Samples are collected using an online questionnaire with 262 respondents, data analysis using (PLS-SEM). The research results show that the intention to use e-wallet is influenced by Effort Expectancy, Performance Expectancy, Price Value, Habit,and Trust. On the other hand, Hedonic Motivation, Facilitating Conditions, and Habit have no effect.